Rehabilitation Following Posterior Shoulder Stabilization - Brandon T Goldenberg; Pamela Goldsten; Lucca Lacheta; Justin W Arner; Matthew T Provencher; Peter J Millett (North American Sports Medicine Institute, 2021)
Posterior shoulder instability has been noted in recent reports to occur at a higher prevalence than originally believed, with many cases occurring in active populations. In most cases, primary surgical treatment for posterior shoulder instability-a posterior labral repair-is indicated for those patients who have failed conservative management and demonstrate persistent functional limitations. In order to optimize surgical success and return to a prior level of function, a comprehensive and focused rehabilitation program is crucial. Currently, there is a limited amount of literature focusing on rehabilitation after surgery for posterior instability. Therefore, the purpose of this clinical commentary is to present a post-surgical rehabilitation program for patients following posterior shoulder labral repair, with recommendations based upon best medical evidence. # Level of Evidence 5